PENGEMBANGAN MULTIMEDIA PENGURANGAN RISIKO BENCANA (PRB) BERBANTUAN MACROMEDIA FLASH BAGI SISWA SD DI WILAYAH RAWAN BENCANA - Dholina Inang Pambudi (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
Abstract This study is a research and development with research subjects consisted of one person matterexperts, two media experts, elementary students. Data collection instrument in the form of sheet materialand expert validation for media experts, a questionnaire to students. Furthermore, the data obtained wereprocessed and analyzed using descriptive statistics as material for revision of the product to be eligible touse for testing in the field so that later could be used as a viable medium used for elementary students. Theresults obtained from research and development are; Multimedia disaster risk reduction is consideredfeasible to use as a learning resource based on the assessment of expert judgment matter experts, mediaexperts, and limited testing on students. Based on expert assessment criteria of the material included in thecategory of "good" with details on aspects of the curriculum mean score of 3.83, 4.00 linguistic aspects,presenting aspects of 4.00, and 4.00 kegrafikan aspects. While the criteria for assessment of media expertsare also included in the category of "good" with details on the mean score 5.00 ease of operation aspects,aspects of display performance of 4.14, 4.00 and benefit aspects. Criteria of "good" is known through theassessment score conversion table value (scale 1-5). Total mean score of students in small groups to testaspects of the product's ease of operation is 4.20, the convenience aspect of the product to be studiedcontents assessment mean score was 4.23, and the attractiveness of the aspects of the display number meanscore was 4.20 all in assessment both categories so that products developed deserves to be widelydisseminated.